If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2 + -1x) = 3(4 + -2x) (2 * 2 + -1x * 2) = 3(4 + -2x) (4 + -2x) = 3(4 + -2x) 4 + -2x = (4 * 3 + -2x * 3) 4 + -2x = (12 + -6x) Solving 4 + -2x = 12 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4 + -2x + 6x = 12 + -6x + 6x Combine like terms: -2x + 6x = 4x 4 + 4x = 12 + -6x + 6x Combine like terms: -6x + 6x = 0 4 + 4x = 12 + 0 4 + 4x = 12 Add '-4' to each side of the equation. 4 + -4 + 4x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = 12 + -4 4x = 12 + -4 Combine like terms: 12 + -4 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| 4+y=-5 | | x/4+1=x | | 15x+(x^2)=64 | | Cx-9x=5 | | .5x(2x-6)=-6 | | 5(x-4)=55 | | 3/10x+14.8=21.2 | | 6x+2x-8=5x-17 | | 1/2t-3.99=4.76 | | 3n-6=-21 | | 9x+29=6x+77 | | 5/6*x-1/5*x+4=7/10*x | | 2x^2+3x^2=144 | | 2a^2+36=18 | | 6=1+4X+x | | -9x+45=x+22.5 | | 18+9d=12d | | 10t+17=-17+12t | | 4x^2-y^2=256 | | 5-x-2y=0 | | -(6y+4)-(5y-7)=1 | | 3b^3+9b=0 | | 121-6x=12x+23 | | 5x+3=7x+-3 | | -6(6y+4)-(-5y-7)=1 | | 3(n+6)=-9 | | 4(7x-1)=3(2x-1)-4(x+6) | | (-2/5)3 | | w^2+16w+64=0 | | 5x+6=106 | | X^2=80X | | 4-3p=-2 |